La responsabilidad compartida en el delito de usura - Coronel Bohorquez, Gissela del Rocio (2014)
This work was carried out with the aim of presenting a legal reform proposal Art. 309 of the Penal Code of Integral , to punish the usurer and the person requesting the money. This organized into six chapters. The first chapter addresses the Research Problem and its corresponding analysis, justification, the definition of objectives and the formulation of the hypothesis. The Second Chapter, refers to the theoretical framework, aspects : historical, doctrinal and legal. The third chapter describes the methodology used in the research at hand ; the methods used , the types of research , population , samples , techniques and instruments used in data collection. The fourth chapter tests the hypothesis through the research results obtained through interviews with relevant authorities based in the cantón Quevedo, in addition to surveys of lawyers in free practice. The fifth chapter describes the conclusions and recommendations. Finally the sixth chapter describes the proposed legal amendment to article 309 of the Penal Code of Integral.